Effect of Working Capital, Debt Maturity, Sales, and Tangibility on Investment Efficiency - Novyarni, Nelli; Christiantoro, Dwi; Harni, Reni (Jurnal EMT KITA, 2023)
The research objective is to analyze variables such as working capital, debt maturity, sales and tangibility that affect investment efficiency. Investment is the activity of placing funds in one or more types of assets for a certain period to earn income. Factors that reflect company performance are the financial statements presented in the annual report. Underinvestment occurs when an investment company requires the use of large amounts of debt. Companies with overinvestment are companies that are in the mature stage with slow growth rates, and high cash flow. In this study the approach used is using quantitative methods. Then analyzed partial and multiple regression. The data used is secondary data. The independent variables used are working capital, debt maturity, sales, and tangibility. The dependent variable used is investment efficiency. The targeted output is to analyze whether the variables of working capital, debt maturity, sales and tangibility affect investment efficiency, so that with this research it is hoped that investment can be efficient.